Decentralization, agricultural services and determinants of input use in Nigeria - Akramov, Kamiljon T. (International Food Policy Research Institute, 2009)
Using a large household survey data, this study examines the impact of government involvement in agricultural service provision on the use of modern inputs by farmers in Nigeria. The empirical methodology used in this study is based on the multilevel (nested) mixed effects estimator and controls for systematic differences and unobserved heterogeneity across sub-national governments. The empirical findings suggest that government involvement in agricultural service provision positively influences the farmers? input use. However, wealthier farmers are more likely than poor farmers to benefit from such services. The likelihood of farmers? input use significantly varies across states and local government areas. Another important finding indicates that the impact of access to all-season roads on input use is heterogeneous across states; it is insignificant in states where the overall likelihood of fertilizer use is relatively high, but becomes significant and positive in states where the overall likelihood of fertilizer use is relatively low.